The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1194/jlr.m500346-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

The predominance of polyunsaturated fatty acids in the butterfly Morpho peleides before and after metamorphosis

Abstract: We hypothesized that the polyunsaturated fatty acids of the butterfly were probably derived from the diet and that there might be a great loss of body fat during metamorphosis. To substantiate these hypotheses, we analyzed the fatty acid composition and content of the diet, the larva, and the butterfly Morpho peleides. Both the diet and the tissues of the larva and butterfly had a high concentration of polyunsaturated fatty acids. In the diet, linolenic acid accounted for 19% and linoleic acid for 8% of total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
1
1

Year Published

2006
2006
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 19 publications
2
24
1
1
Order By: Relevance
“…We here provided adult female butterflies with a mixture of linoleic acid, linolenic acid, arachidonic acid and eicosapentaenoic acid. Linoleic and linolenic acids are the most abundant PUFAs found in caterpillars and adult butterflies (Wang et al, 2006), and both are thought to adequately satisfy the nutritional need for PUFAs in most species and references therein). Further, they are considered essential fatty acids for many insect species (Beenakkers et al, 1985).…”
Section: Effects On Longevity and Reproductionmentioning
confidence: 99%
“…We here provided adult female butterflies with a mixture of linoleic acid, linolenic acid, arachidonic acid and eicosapentaenoic acid. Linoleic and linolenic acids are the most abundant PUFAs found in caterpillars and adult butterflies (Wang et al, 2006), and both are thought to adequately satisfy the nutritional need for PUFAs in most species and references therein). Further, they are considered essential fatty acids for many insect species (Beenakkers et al, 1985).…”
Section: Effects On Longevity and Reproductionmentioning
confidence: 99%
“…Furthermore, this 'U-shaped' pattern is correlated to a higher oxygen consumption as well as to the needs in lipids during the first stages of metamorphosis. On the other hand, species store lipid just before adult eclosion as an energy store for the forthcoming needs of flight (D'Costa and Birt, 1966;Law, 1980;Peakin et al, 1989;Nation, 2002;Nestel et al, 2004;Wang et al, 2006;Papanastastasiou et al, in press).…”
Section: Discussionmentioning
confidence: 96%
“…Thus, the butterfly must lose considerable fat tissue during flight. In our recent report, we found that larva lost large amounts of fat during metamorphosis (10). However, the larva and butterfly have similar total sterol contents, 325 and 380 mg (Tables 2, 4).…”
Section: Discussionmentioning
confidence: 99%
“…We found no information in the literature about the sterol composition of the butterfly before and after metamorphosis and no information about how the diet of the larva might influence its sterol composition. In a recently published study, we found that the butterfly drastically decreases its body weight and body fat during metamorphosis (10).…”
mentioning
confidence: 99%